Đặc điểm hình thế thời tiết gây mưa, lũ, lụt lớn và đặc biệt lớn các tỉnh Quảng Bình, Quảng Trị, Thừa Thiên - Huế - Vân, Nguyễn Khanh; Tăng, Bùi Minh (Vietnam Journal of Earth Sciences, 2003)
The characteristics of weather synoptic situations causing very heavy rains, serious inundation, and floods in euang Binh, euang Tri and Thua Thien - Hue